Arctic char ( Salvelinus alpinus ) metallothionein: cDNA sequence, expression, and tissue-specific inhibition of cadmium-mediated metallothionein induction by 17β-estradiol, 4-OH-PCB 30, and PCB 104 - Gerpe, Marcela Silvia (2000)
In this study, we haveexamined the basallevel expression and tissue‐specificexpressionpatternsof metallothionein (MT) in Arctic char following metal and E2 (17β‐estradiol) treatment. To study the gene regulation in Arctic char, the two MT isoforms were isolated from a lambda‐ZAP hepatic cDNA library and characterized. Determination of basal MT mRNA and MT expression for 10 different tissues revealed a lack of correlation between MT mRNA and MT levels. The inducibility of MT mRNA and the correlation to resulting MT levels were then determined for liver and kidney. We found a more rapid and stronger induction of MT mRNA in liver than in kidney at day 1 and 3 postinjection, whereas the MT protein quantification showed higher MT levels in kidney than in liver at days 3 and 7 postinjection. These discrepancies indicate that differences in metal handling or posttran‐scriptional regulation of MT exists between tissues. Whereas metals induce MT synthesis, E2 inhibit the hepatic MT expression. To examine the tissue specificity of this inhibition, we determined the effect of 17pj‐estradiol (E2) and two estrogenic PCBs (4′‐OH‐PCB 30 and PCB 104) on Cd‐mediated MT induction in liver and kidney. Although E2 and the estrogenic PCBs inhibited cadmium‐mediated hepatic MT induction, these compounds did not interfere with renal MT induction.